Electron Solvation and the Unique Liquid Structure of a Mixed‐Amine Expanded Metal: The Saturated Li–NH3–MeNH2 System. (10th January 2017) - Seel, Andrew G.; Swan, Helen; Bowron, Daniel T.; Wasse, Jonathan C.; Weller, Thomas; Edwards, Peter P.; Howard, Christopher A.; Skipper, Neal T.
Abstract: Metal–amine solutions provide a unique arena in which to study electrons in solution, and to tune the electron density from the extremes of electrolytic through to true metallic behavior. The existence and structure of a new class of concentrated metal‐amine liquid, Li–NH3 –MeNH2, is presented in which the mixed solvent produces a novel type of electron solvation and delocalization that is fundamentally different from either of the constituent systems. NMR, ESR, and neutron diffraction allow the environment of the solvated electron and liquid structure to be precisely interrogated. Unexpectedly it was found that the solution is truly homogeneous and metallic. Equally surprising was the observation of strong longer‐range order in this mixed solvent system. This is despite the heterogeneity of the cation solvation, and it is concluded that the solvated electron itself acts as a structural template. This is a quite remarkable observation, given that the liquid is metallic.